Phản ứng quang hoá và ozon hoá của các dẫn xuất 12-deoxoartemisinin - Quân, Trần Đức; Sung, Trần Văn (Vietnam Journal of Chemistry, 2014)
The compounds 12’-allyldeoxoartemisinin and anhydroartemisinin have been synthetized under mild conditions with high yield. Ozonolyse of 12’-allyldeoxoartemisinin and anhydroartemisinin as well as the photolyse of 12’-allyldeoxoartemisinin were carried out. All the reactions gave good yield. This is the first time the ozonolyse of anhydroartemisinin and the photolyse of 12’-allyldeoxoartemisinin have been reported.